Tuning dual-Fe sites in Fe–N–C dual-atom catalysts by sulfur doping for enhanced CO₂ electroreduction: Insights from the first-principles computations - Manal B. AlHamdan (22150285) (2025)
This study explores the impact of sulfur doping on the surface and electronic structure of Fe–N–C dual-atom catalysts for electrochemical CO2 reduction, using first-principles density functional theory (DFT) computations. By introducing one or two sulfur atoms near the catalytically active Fe centers, we systematically assess changes in geometry, electronic structure, and adsorption behavior. Sulfur incorporation significantly modifies the local electronic environment, notably increasing the density of states near the Fermi level and enhancing charge redistribution at the active sites. These effects result in stronger and more selective adsorption of key reaction intermediates, including CO2, *COOH, and *CO2 as revealed by adsorption energy and charge density analyses. Dual-sulfur doping, in particular, leads to marked improvements in intermediate stabilization, indicating a synergistic effect on catalytic performance. These findings highlight the potential of surface heteroatom doping as an effective strategy for tailoring the activity and selectivity of transition-metal-based catalysts, providing valuable guidance for the rational design of advanced electrocatalysts for CO2 electroreduction. Other Information Published in: Surfaces and Interfaces License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.surfin.2025.107310